SOME ASPECTS OF THE BIOLOGY OF JOHNIEOPS SINA (CUVIER, 1830) FROM MUMBAI WATERS - Telvekar, Prashant; Biradar, R. S.; Chakraborty, S. K.; Jaiswar, A. K.; Rathod, Rajeev (Journal of Indian Fisheries Association, 2006)
Investigations on food and feeding of Johnieops sina indicated that it feedsmainly on penaeid prawns, Acetes spp. and fishes. Penaeid prawns were found to be its preferred food item. The spawning activity was observed throughout the year with two peaks in February and August, supported by prominent peaks of gonadosomatic index in the same months. The minimum size at first maturity for females was 153 mm. The absolute fecundity ranged from 28,495 to 135,346 eggs for the ovaries weighing 1.30 to 9.49 g.Keywords: Johnieops sina, food and feeding habit, spawning season, firstmaturity, sex ratio, fecundity